The Effect Of Fear Of Missing Out (Fomo), Flash Sale, And Social Influence On Skincare Product Purchase Decisions At Tiktok Shop (A Study On Generation Z In Surabaya) - Shaffa Arisqha Maghfiroh Putri; Maharani Ikaningtyas (UNIVERSITAS PAKUAN, 2026)
The increasing use of TikTok Shop has driven changes in consumer purchasing behavior, particularly among Generation Z when buying skincare products. This study aims to analyze the influence of Fear of Missing Out (FoMO), Flash Sales, and Social Influence on purchase decisions for skincare products on TikTok Shop among Generation Z in Surabaya. This study employs a quantitative approach using a survey method. The research sample consisted of 157 respondents determined using the Slovin formula. The sampling technique used non-probability sampling with a purposive sampling method, specifically targeting Generation Z in Surabaya who had previously purchased skincare products on TikTok Shop. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression with the aid of SPSS. The results of this study indicate that Fear of Missing Out, Flash Sales, and Social Influence have a positive and significant effect on Purchase Decisions, both partially and simultaneously. This study demonstrates that marketing strategies based on urgency and social influence can increase the purchase of skincare products among Generation Z on TikTok Shop